Sistem Informasi Inventory Pengeboran Minyak Menerapkan Metode Material Requirement Planning (MRP) - Rice Novita; Ressy Afrianti (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2012)
Inventory Information System is an information system which manages data transactions and inventory in the warehouse. Implementation of this research was conducted at TIMAS SUPLINDO Duri. TIMAS SUPLINDO Duri is one of the contractors company which cooperate with Chevron and focus on oil drilling is engaged in oil drilling. Inventory of material on TIMAS SUPLINDO Duri not be well planned so that the inventory of existing materials in the company is often a delay in delivery so that the oil drilling process could not proceed smoothly. Objectives to be achieved in this study was to plan the inventory of materials used in oil drilling process which is on TIMAS SUPLINDO thorns. Reasons for using the method of Material Requirements Planning (MRP) is expected to take into account the amount of material goods with the required capacity of production and material procurement time appropriately based on the size and type specified.The output is obtained using the method of material requirements planning (MRP) was able to determine what, when, and how the number of components and materials required to meet the needs of a production planning oil drilling.Key words: Inventory, Material Requirements Planning (MRP), TIMAS SUPLINDO Duri,